LINNAEUS AND HIS CONTRIBUTION TO BACTERIAL TAXONOMY - Padrón López, Rosa Martha; Vázquez Cruz, Lucero; Lesher Gordillo, Julia María; Sánchez Ordoñez, Abril (Kuxulkab’, 2024)
Microbial taxonomy has undergone important changes over the course of time since the discovery of the microscope, which led to the observations of microorganisms, called animalcules. In the first attempts to classify bacteria, under the system proposed by Carl Nilsson Linnaeus, they were considered as eukaryotic organisms. The development of the microscope and the improvement of its lenses made it possible to describe, in greater detail, their size, structure and morphology; facts of great value in recognizing bacteria as prokaryotic cells. In recent years, bacterial taxonomy is performed with a polyphasic approach in which conventional or classical methods are used, in addition, to molecular tools such as the use of ribosomal genes or specific genes, bioinformatics tools and molecular databases that together allow the identification of bacteria.